POLICY AND IMPLEMNTATION OF LAW NUMBER 33 OF 2014 CONCERNING HALAL CERTIFICATE - Harahap, Syahrul Bakti; Perdana, Surya; Wadji, Farid (Proceeding International Seminar of Islamic Studies, 2024)
The Indonesia Govermet has made a policy regarding halal certifcates on products insirculation both food, drinks, medicines, and cosmetics. Products  cirkulating, entering, and trading in Indonesia teritory must be halal certificates, law number 33 of 2014, regarding halal certification gives authority to Ministry Religion of the Republic Indonesia namely the halal Product Guaratee Management Agency (BPJPH). Based on article 5 paragra (5), of law number 33 of 2014, BPJPH aoutority consist of: a) Formulate and estabilish a halal product guarantee (JPH) policy. b) Estabilish norm, standars, prosedures, and JPH performance. c) issuing and revoking halal certificat. d)  registering halal seritificat  for foreign roducts. To implemet halal certification, BPJPH collaborates with related ministeries and institution, insttution halal inspector (LPH), and the Indonesia Ulama Councul (MUI), based on law number 33 of 2014. The issuance of halal sertification has shifted from MUI to BPJPH. After condukting research based on library reseach the is one of the resons the goverentment is moving the halal certifcation policy from MUI to BPJPH is that money resultig halal certificatio cannot be audited, because MUI is not goverentment body, acording to reseachers this policy is not appropriate.